The Algorithm of Fear: Unpacking Prejudice Against AI and the Mistrust of Technology - Hutson, James; Plate, Daniel (INTI International University, 2024)
The mistrust of AI seen in the media, industry and education reflects deep-seated cultural anxieties, often comparable to societal prejudices like racism and sexism. Throughout history, literature and media have portrayed machines as antagonists, amplifying fears of technological obsolescence and identity loss. Despite the recent remarkable advancements in AI—particularly in creative and decision-making capacities—human resistance to its adoption persists, rooted in a combination of technophobia, algorithm aversion, and cultural narratives of dystopia. This review investigates the origins of this prejudice, focusing on the parallels between current attitudes toward AI and historical resistance to new technologies. Drawing on examples from popular media and recent research, the article reveals how AI, despite outperforming humans in some creative tasks, is often undervalued due to bias. The evidence shows that the tool can significantly augment human creativity and productivity, yet these benefits are frequently undermined by persistent skepticism. The article argues that this prejudice represents a critical barrier to the full realization of the potential of the generative technology and calls for a reexamination of human-AI collaboration, emphasizing the importance of addressing these biases both culturally and within educational and professional frameworks.